2020
DOI: 10.1016/j.idairyj.2020.104655
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the bovine milk fatty acid profile – From colostrum to milk five days post parturition

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 48 publications
10
40
2
Order By: Relevance
“…Supplementation of ALA by the EFA treatment resulted in a 19-fold increase of ALA in colostrum fat of EFA-cows when compared with CTRL cows (0.07 ± 0.11% and 1.34 ± 0.10% for CTRL and EFA, respectively; Supplemental Table S3; Vogel et al, 2020). Concentration of ALA in colostrum fat was slightly higher than in milk fat of cow fed fresh grass or on pasture (ALA in milk fat: 0.7-1.12%; Kelly et al, 1998;Kay et al, 2005;Couvreur et al, 2006), but in a recent study a greater EFA content in colostrum than mature milk in dairy cows was shown (O'Callaghan et al, 2020). Therefore, the FA supply via colostrum and transition milk determined the ALA status of the neonatal calf in the present study.…”
Section: Effects On Fa Profiles In Blood Plasma After Milk Feedingmentioning
confidence: 89%
“…Supplementation of ALA by the EFA treatment resulted in a 19-fold increase of ALA in colostrum fat of EFA-cows when compared with CTRL cows (0.07 ± 0.11% and 1.34 ± 0.10% for CTRL and EFA, respectively; Supplemental Table S3; Vogel et al, 2020). Concentration of ALA in colostrum fat was slightly higher than in milk fat of cow fed fresh grass or on pasture (ALA in milk fat: 0.7-1.12%; Kelly et al, 1998;Kay et al, 2005;Couvreur et al, 2006), but in a recent study a greater EFA content in colostrum than mature milk in dairy cows was shown (O'Callaghan et al, 2020). Therefore, the FA supply via colostrum and transition milk determined the ALA status of the neonatal calf in the present study.…”
Section: Effects On Fa Profiles In Blood Plasma After Milk Feedingmentioning
confidence: 89%
“…The lipid fraction contains multiple components of potential health relevance, including ω-3 and ω-6 polyunsaturated fatty acids, conjugated linoleic acid, short chain fatty acids, gangliosides, and phospholipids. Fatty acid constituents of BC are approximately 65–75% saturated, 24–28% monounsaturated and 4–5% polyunsaturated [ 33 , 34 ], and the predominant fatty acids are palmitic and oleic, accounting for 40% and 21% of total fatty acids, respectively [ 34 ]. The fat component of BC is often removed from commercial preparations to aid stability and processing; however, it is not biologically inert.…”
Section: Constituents Of Bcmentioning
confidence: 99%
“…Colostrum (immediately after parturition) typically has a higher fat content than transition milks (days 1–5 postpartum) [ 37 ] and mature milks [ 38 ]. In mature milk, early lactation coincides with the lowest milk fat content, despite being the period where the highest milk fat yields are achieved [ 5 , 6 , 24 ].…”
Section: Milk Compositionmentioning
confidence: 99%
“…Mid and late lactation milks however, were characterised by eicosatrienoic acid (C20:3), erucic acid (C22:1), palmitic acid (C16:0) and LA (C18:2) when consuming TMR and pentadecanoic acid (C15:0), tridecanoic acid (C13:0), tricosanoic acid (C23:0), linolenic acid (C18:3), CLA (C18:2 cis -9, trans -11), arachidonic acid (C20:4), undecanoic acid C11:0, and linolelaidic acid (C18:2) when consuming pasture diets [ 5 ]. O’Callaghan et al [ 37 ] demonstrated an increasing UFA content and decreasing SFA content between colostrum and milk 5 days post parturition.…”
Section: Milk Compositionmentioning
confidence: 99%